Evolution of tropical cyclone genesis regions during the Cenozoic era - Qing Yan (Nature Portfolio, 2019)
Model simulations show that tropical cyclones were preferably formed in the Southern Hemisphere during the warmer Early Eocene, but then shifted along a cooling climate across the Cenozoic to the Northern Hemisphere. Today's conditions favoring the western North Pacific as the largest genesis center is a result of closing tropical seaways during the Pliocene.